REFLECTION ON ECOLOGICAL LEARNING THROUGH ARCHITECTURAL DESIGN STUDIO - Diandra Pandu Saginatari; Paramita Atmodiwirjo (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2018)
Architecture, both in the practice and the education, is moving toward a higher environmental awareness. It is shown from the inclusion of ecology as one of the core subject in the curriculum. But, ecology is dominantly viewed and learned through a scientific and qualitative approach rather than a creative design methodology. This paper argues that ecology always has a potential to become the basis of creative design process. There are three key aspects in learning ecology in architecture: learning ecology as reading complexity, as understanding dynamicity, and as building up awareness of our position as designers. These key learning aspects are enabled by the nature of architectural design studio as educational environment. This paper examines the key aspects of ecological learning within one of the design studio in Universitas Indonesia. The study concludes that there is a relationship between the learning stages of the design project and the ecological understanding of the students.